2016
DOI: 10.3389/fmicb.2016.00405
|View full text |Cite
|
Sign up to set email alerts
|

Novel Anti-Campylobacter Compounds Identified Using High Throughput Screening of a Pre-selected Enriched Small Molecules Library

Abstract: Campylobacter is a leading cause of foodborne bacterial gastroenteritis worldwide and infections can be fatal. The emergence of antibiotic-resistant Campylobacter spp. necessitates the development of new antimicrobials. We identified novel anti-Campylobacter small molecule inhibitors using a high throughput growth inhibition assay. To expedite screening, we made use of a “bioactive” library of 4182 compounds that we have previously shown to be active against diverse microbes. Screening for growth inhibition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 43 publications
0
41
0
3
Order By: Relevance
“…These tests determined the lowest concentrations of each compound to cause the death of human colon cells after a 72 h treatment with each of the compounds separately, using a sulphorodhamine assay. Details of these determinations are reported in a previous publication . The results showed that the values for JA‐144, TH‐4, and TH‐8 were 200 µM.…”
Section: Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…These tests determined the lowest concentrations of each compound to cause the death of human colon cells after a 72 h treatment with each of the compounds separately, using a sulphorodhamine assay. Details of these determinations are reported in a previous publication . The results showed that the values for JA‐144, TH‐4, and TH‐8 were 200 µM.…”
Section: Methodsmentioning
confidence: 85%
“…These microorganisms appeared not to develop antimicrobial resistance to these small molecules, when compared to other regularly used antimicrobial agents. These small molecule compounds were selected after a high throughput screening of a library of ≈4,200 compounds …”
Section: Methodsmentioning
confidence: 99%
“…Bioluminescence of SMs treated culture supernatants were compared to DMSO treated control. The Z-score was calculated to evaluate the quality of the bioluminescence screening [56]. Four independent experiments were conducted for the 69 compounds that inhibited ≥ 75% of the AI-2 mediated bioluminescence and the average inhibition percentage was calculated.…”
Section: Ai-2 Bioluminescence Indicator Assaymentioning
confidence: 99%
“…The selected 10 AI-2 inhibitors were evaluated for their toxicity to Caco-2 (ATCC® HTB-37™) using LDH assay [56]. Briefly, Caco-2 cells (1.4 × 10 5 cells/well) were grown in a 96-well plate in minimal essential medium (MEM) supplemented with 20% fetal bovine serum (FBS; Gibco), 1% non-essential amino acid (NEAA, Invitrogen Life Technologies) and 1mM sodium pyruvate, at 37°C in a humidified 5% CO 2 incubator for 48 h until a complete monolayer was formed.…”
Section: Lactate Dehydrogenase Assaymentioning
confidence: 99%
“…Taken together, these observations indicate that the development of novel antimicrobials for the reduction or treatment of human Campylobacter infections is necessary (7). Several avenues of reducing the incidence of human campylobacteriosis have been pursued at various levels of the infectious cycle (3).…”
Section: Introductionmentioning
confidence: 99%